Flow behaviour of TiHy 600 alloy under hot deformation using gleeble 3800. Issue 4 (2nd October 2017) - Kodli, Basanth Kumar; Karre, Rajamallu; Saxena, Kuldeep K.; Pancholi, Vivek; Dey, Suhash R.; Bhattacharjee, Amit
Abstract: To understand deformation behaviour of TiHy 600 alloy at higher temperatures, hot compression tests are performed in α region (1173 K), α + β regions (1223, 1248, and 1273 K) and β region (1323 K) at strain rates (0.001, 0.01, 0.1, 1 and 10/s) for up to 50% deformation in Gleeble 3800 ® thermo-mechanical simulator. Flow curve plots are drawn at each strain rates and temperatures and it is observed that dominant deformation mechanism at higher temperature 1323 K ( β region) and strain rates (1 and 10/s) is dynamic recovery (DRV) whereas dynamic recrystallization (DRX) is mostly observed at lower strain rates (0.001, 0.01/s) in medium temperature range of 1223 K ( α region) to 1248 K ( α + β region). Hyperbolic sine law equation is used to calculate the activation energy ( Q ) and other material sensitive parameters ( A, α and n 1 ). The activation energies for DRX in α region and DRV in β region are obtained as 384 and 251 kJ/mol. Experimental peak stress values are compared with predicted peak stress values ( R 2 = 96.2%) and Zener-Hollomon parameter ( R 2 = 94.3%). The flow stress behavior up to the peak stress is verified with Cingara equation. Finally, calculated prediction results of DRX volume fraction obtained from Avrami equation is compared with experimental observed microstructure.